A novel mouse model of anterior segment dysgenesis (ASD): conditional deletion of Tsc1 disrupts ciliary body and iris development - Anna-Carin Hägglund; Iwan Jones; Leif Carlsson (Disease Models & Mechanisms, 2017)
Development of the cornea, lens, ciliary body and iris within the anterior segment of the eye involves coordinated interaction between cells originating from the ciliary margin of the optic cup, the overlying periocular mesenchyme and the lens epithelium. Anterior segment dysgenesis (ASD) encompasses a spectrum of developmental syndromes that affect these anterior segment tissues. ASD conditions arise as a result of dominantly inherited genetic mutations and result in both ocular-specific and systemic forms of dysgenesis that are best exemplified by aniridia and Axenfeld–Rieger syndrome, respectively. Extensive clinical overlap in disease presentation amongst ASD syndromes creates challenges for correct diagnosis and classification. The use of animal models has therefore proved to be a robust approach for unravelling this complex genotypic and phenotypic heterogeneity. However, despite these successes, it is clear that additional genes that underlie several ASD syndromes remain unidentified. Here, we report the characterisation of a novel mouse model of ASD. Conditional deletion of Tsc1 during eye development leads to a premature upregulation of mTORC1 activity within the ciliary margin, periocular mesenchyme and lens epithelium. This aberrant mTORC1 signalling within the ciliary margin in particular leads to a reduction in the number of cells that express Pax6, Bmp4 and Msx1. Sustained mTORC1 signalling also induces a decrease in ciliary margin progenitor cell proliferation and a consequent failure of ciliary body and iris development in postnatal animals. Our study therefore identifies Tsc1 as a novel candidate ASD gene. Furthermore, the Tsc1-ablated mouse model also provides a valuable resource for future studies concerning the molecular mechanisms underlying ASD and acts as a platform for evaluating therapeutic approaches for the treatment of visual disorders.